PENGARUH PEMBERIAN PAKAN KOMPLIT HASIL SAMPING UBI KAYU KLON TERHADAP PERTUMBUHAN DOMBA JANTAN LOKAL - Janwar Hamonangan Tampubolon (Jurnal Peternakan Integratif, 2014)
ABSTRACT   JANWAR HAMONANGAN TAMPUBOLON , 2014 " the effect of feeding cassava complete results on growth of local Ram. Guided by R.Edhy Mirwandhono as chairman of the supervising committee and as a member of the commission Ma'Ruf Tafsin supervisor.consumption, body weight gain, and feed conversion of local ram. Byproducts of cassava can daily body weight growth of sheep. The experiment was conducted at the Faculty of the University of North Sumatra pertanaian September to December 2013 . The design used in this research is completely randomized design (CRD) with 3 treatments . This treatment consists of p1 : (100 % grass), p2 (50 % grass and 50 % byproduct of cassava pellets) ; (p3 100 % cassava feed byproduct) . The results showed the  Effect of Feeding Cassava Side average feed consumption ( g / head / day ) 518.27 , 316.2075 and 255.1325 . respectively growth of body weight 466.25 ; 543.5 and 767.75, respectively Feed conversion 15.445 ; 8.0445 ; 4.7025. Statistical test results showed  cassava feeding  significantly affect feed intake ,  body weight , and feed conversion This study aims to determine Conclusions from the study of feeding cassava by product of a very real effect on consumption , body weight , and conversion Keywords : Cassava, Byproduct, Local Lamb.